Employee attribution strengthening training as an effort to support persebaya cooperative competitiveness - Sanjaya, Agus; Kurniawan, Gogi (Enrichment : Journal of Management, 2023)
Cooperatives in the community empowerment sector need to be supported by credible human resources in order to remain able to survive in the midst of market competition, moreover the types of products produced are a need for style and identity in the identified market segments. This study aims to examine the effect of employee self-attribution training on increasing attributions that support cooperative competitiveness. This experimental research took 10 members of the Persebaya Cooperative management. Self attribution strengthening training was given locus of control (LoC) and need for achievement (N-Ach) materials. The results of the pre-test and post-test of paired samples obtained t = 12.628 and p = 0.002 (p <0.05) meaning that there was an increase in employee self-attribution after training. The increase in self-attribution was shown by the increase in the average N-Ach and LoC values, both of which showed significant changes. Spearman_rho correlation analysis results obtained r = 0.743 with p = 0.002 (p <0.05) indicating a positive and significant correlation between LoC and N-Ach. The coefficient of determination of 0.552 explains that LoC makes an effective contribution to N-Ac of 55.2%. The results of this study can be concluded that self-attribution strengthening training with N-Ach and LoC material for employees can have an impact on increasing attribution that supports the competitiveness of the Persebaya cooperative which is able to explain HR competencies.